The importance of corporate social responsibility on company performance in Malaysia - Perumal, Selvan; Othman, Abdul Rahim; Mustafa, Saed Adnan (Academic Research Publishers, 2013)
The concept of social responsibility of corporations has engendered considerable interest in Malaysia in recent years.While previous research on the relationship between corporate social responsibility and company performance has largely been based on international data, this paper reviews the relationship between the adoption of corporate social responsibility dimensions and the company performance of public listed companies. 200 responses were received from a population that had already working in Malaysian public listed companies.The results derived from multi-group structural equation modeling within AMOS 7.0. Furthermore this paper found a significant relationship between economic, philanthropic and company performance.The findings imply the need for public listed companies, particularly main and ACEboard, to strategically leverage the effect of CSR on company performance.